Simile Language Style in the Text of Babad Tanah Jawi Balai Pustaka Version - R. Adi Deswijaya; Agus Efendi; Bambang Ikhwanto; Pradnya Paramita Hapsari; Niken Habsari Ayuningtyas; Muhammad Ridwan (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2026)
This stylistic study focuses on the form and function of simile motifs found in the Balai Pustaka edition of Babad Tanah Jawi, Volume 1. The primary emphasis is on recognizing the kinds of simile motifs employed and their artistic and rhetorical purposes. The method used was a qualitative descriptive approach, involving reading and recording data from the text, which was then analyzed using distribution and correspondence techniques related to the theory of simile as a figure of speech. The findings reveal that among the 54 analyzed data points, six prevalent simile motifs emerged: (1) depicting beauty, (2) signaling effects, (3) enhancing character, (4) visualizing objects, (5) conveying inner emotions, and (6) portraying chaos or scale. The prevailing simile language is lir, showcasing a conventional trend in Javanese classical literary analogies. Similes in the text serve as both artistic elements and tools that enhance meaning and create vivid imagery of characters and situations. This research validates the crucial function of similes in influencing the expressive and artistic strength of classical Javanese literature.